Review on SR- Tech Solution - Satvaya, S; s, Shambhavi; Goyal, R; Parajuli, R; Jhingran, S (International Journal of Computer Sciences and Engineering, 2021)
The current education system is getting digitized at a very fast pace. Administrators of Educational institutions have become increasingly concerned about regularity of student attendance and their overall academic performance. In the earlier times, attendance record and performance evaluation was carried out manually like writing down the data using pen and paper. Most of the school’s students and faculty are using iOS, Android and other LMS application based applications. The authors propose to develop application software for the college/university administration. The authors propose to use advanced java and other integrated technologies to develop the application that deals with the all the College/University related work. Administrative data needs to be digitized for the management to get accurate and up-to-date information regarding a student’s academic career.